2019
DOI: 10.1098/rsos.190769
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing gold nanoparticles for use in X-ray computed tomography imaging of soil systems

Abstract: This investigation establishes a system of gold nanoparticles that show good colloidal stability as an X-ray computed tomography (XCT) contrast agent under soil conditions. Gold nanoparticles offer numerous beneficial traits for experiments in biology including: comparatively minimal phytotoxicity, X-ray attenuation of the material and the capacity for functionalization. However, soil salinity, acidity and surface charges can induce aggregation and destabilize gold nanoparticles, hence in biomedical applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…1c) -the roots extending from the base were thus submerged in the contrast media. This concentration was determined by previous work (Scotson et al 2020) and was confirmed as appropriate with the use of a phantom containing the contrast media and soil which displayed sufficient contrast between materials. The phantom consisted of a length of syringe identical to those used for the root growth chamber.…”
Section: Addition Of Contrast Mediasupporting
confidence: 65%
See 3 more Smart Citations
“…1c) -the roots extending from the base were thus submerged in the contrast media. This concentration was determined by previous work (Scotson et al 2020) and was confirmed as appropriate with the use of a phantom containing the contrast media and soil which displayed sufficient contrast between materials. The phantom consisted of a length of syringe identical to those used for the root growth chamber.…”
Section: Addition Of Contrast Mediasupporting
confidence: 65%
“…3). Additionally, with the development of nanoparticulate contrast media for use in soil (Scotson et al 2019), it is possible that in future the in vivo anatomical imaging achievable with our experimental system could be further enhanced with the use of nanoparticles functionalised to accumulate on particular plant tissues or organs. Particularly with the use of nanoparticles of approximately 3.5 nm in size, which have previously been observed to pass into roots and then be translocated throughout the plant to the leaves (Sabo-Attwood et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The organic matter contents were 2.3% and 5.5%, and the pH was 6.35 and 6.5 for the LS and CL, respectively. The water‐extractable phosphorus (P) was 530 ppb for the LS (Scotson et al , 2019). No P information was available for the clay‐loam; however, both soils were taken from the same field.…”
Section: Methodsmentioning
confidence: 99%